Strategic conversations : creating and directing the entrepreneurial workforce - Spender, J.-C; Strong, Bruce A. (Cambridge : Cambridge University Press, 2014)
Most organizations fail to take full advantage of their employees' knowledge, initiative, and imagination. In this accessible and practical book, J.-C. Spender and Bruce Strong provide a guide for building entrepreneurial workforces through carefully designed conversations between management and employees. These'strategic conversations' make employees partners in the strategy development process, engaging them to help shape the organization's future. The result is transformational: instead of strategy being a dry, periodic planning exercise for the few, it becomes a dynamic and continuous act of co-creation enriched by the many. Case studies illustrate how leading organizations have used strategic conversations to build sustained competitive advantage, create innovative business models, make better decisions under uncertainty, reduce the need for change management, and enhance employee engagement. The book will appeal to managers, entrepreneurs of all stripes, and teachers and students in schools of business and public administration.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Strategic planning; Human capital -- Management; Knowledge management; Organizational effectiveness; Organizational behavior